STRAIN ANALYSIS OF REACTOR TYPE CORE STRUCTURES BY CONSIDERING UNCERTAINTIES OF GRAPHITE’S PROPERTIES - Mike Susmikanti; Roziq Himawan; Jos Budi Sulistyo; Farisy Yogatama Sulistyo (Pusat Teknologi Dan Keselamatan Reaktor Nuklir (PTKRN), 2021)
The power reactor with high-temperature gas-cooled reactor (HTGR) technology uses uranium as the reactor fuel. The energy from fission is converted to electrical energy or used for other needs such as hydrogen production or other research activities at high temperatures of around 700 °C. This operation does not allow the use of metal as the core material for the reactor. The material that fits the requirements as a core structure is graphite. Graphite material has specific characteristics, namely the parameters of the modulus of elasticity, coefficient of thermal expansion, and the volume which changes due to temperature and neutron dose. Because the structure of the reactor core is a vital component in the reactor, this research will develop a method for the design of the reactor core structure with graphite material. The design method is based on